Application of a multienzymatic system from natural latex in key reactions for oil-based biorefineries - Sanchez, Daniel Alberto (2019)
Oil-based biorefineries play a crucial role in the production of key platform chemicals that can be generated via biotechnological processes instead of a petrochemical route. This work focuses on the latex of the fruit of Araujia sericifera, which can be considered a multienzymatic system with applications in key reactions in oil-based biorefineries. The latex of Araujia sericifera (ASL) was used as a novel biocatalyst in the esterification of oleic acid and in the hydrolysis of triglycerides and p-nitrophenyl carboxylates. When ASL was compared to a commercial biocatalyst, it showed an excellent activity in the hydrolysis of soybean oil and p-nitropheyl laurate, and a comparable activity in the esterification reaction.